Analysis of Project-Based Learning Design Needs: Building Students' Creative Thinking Skills and Independent Learning - Sundari, Ayu; Yennita, Yennita; Syafii, Muhammad (Journal of Educational Sciences, 2025)
The ability to think creatively and learn independently is an important factor in student success in the learning process. One model that plays an important role in increasing creative thinking and independent learning is the project based learning (PjBL) model. This research aims to analyze the needs for project-based learning design to improve creative thinking abilities and learning independence. The research was conducted at a high school in Pekanbaru involving 76 students. Data collection methods use closed and open questionnaires. The research results show that project model learning is a model that many students are interested in. In the open-ended question, most students were interested in PjBL learning, which was 25 people. In the open-ended question, 64.5% agreed that the physics project helped them disseminate their understanding. Apart from that, students' creative thinking abilities and learning independence are not yet optimal, so it is necessary to design a learning model that is popular and can improve students' creative thinking abilities and learning independence.